Development of Strategic Human Resource Management towards Improvement Work Culture at Baitul Mal in Aceh - Mukhsinuddin, Mukhsinuddin; Rinaldi, Mikral; Yanto, Yanto; Aprilian, Rahil Imainul (Universitas Bangka Belitung, 2023)
This study aims to determine Human Resource management and strategy in developinga performance culture at Baitul Mal throughout Aceh Province. Approach, directionand human resources synergize to achieve a goal and have great potential to manageBaitul Mal in Aceh Province as an Islamic Sharia Region. Therefore, researchers areinterested in researching how the strategy of human resources in the Baitul Mal of theProvince of Aceh in improving the welfare of the community regarding themanagement of Zakat, Infaq, and Sadaqah (ZIS) funds in the Province of Aceh. Theapproach used in this research is qualitative. While the methods used are observation,in-depth interviews, and documentation studies. This research also collected data fromthe Baitul Mal of Aceh Province, West Aceh, South Aceh, and the Municipality ofBanda Aceh